Abraha the Abyssinian in Islamic tradition - van Donzel, Emeri (Aethiopica, 2009)
Abraha, the Abyssinian ruler of Yemen, who dared to attack Mecca in an attempt to demolish the sacred Kaʿba, is well known in Muslim historical traditions about pre-Islamic Arabia (Sīra and ḥadīṯ). The article presents a collection of the most significant Islamic texts related to Abraha and his military adventure. The author explains how the image of the Ethiopian army commander was blended into the traditional Islamic eschatological personage of the Abyssinian “with the two small shanks” who will destroy the sanctuary of Mecca before the end of the world. Moreover, the descriptions of the characteristics of these two individuals are analyzed in detail to highlight the fact that there is a clear difference between the report of Abraha’s actions in the more historically oriented sources (Sīra) and the harsh judgment against him in the definitely more religiously marked prophetic sayings (ḥadīṯ). ATTENTION: Due to copy-right no online publication is provided.